1976
DOI: 10.1161/01.str.7.5.485
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarction in the Mongolian gerbil exacerbated by phenoxybenzamine treatment.

Abstract: In a double-blind study, the effects of a large dose (20 mg per kilogram) of phenoxybenzamine (PBZ) on cerebral infarction were evaluated in 120 Mongolian gerbils. The left common carotid artery was ligated in 100 animals; a sham operation was done in 20 animals. One hour later, 25 animals were given 2 mg per kilogram of PBZ, 25 animals were given 20 mg per kilogram of phenoxybenzamine, and 50 animals were given 0.5 cc of nomal saline, all doses being repeated at 24, 48, and 72 hours. Five sham-operated animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…Our previous autoradiographic assessment with 14 Cantipyrine" revealed a marked rCBF increase in the ischemic hemisphere of gerbils that had been exposed to 1 h ischemia when the systemic blood pressure was elevated to 130-150 mm Hg after blood flow restoration. In the same study, diffuse oligemia was noted in This led to the consideration that a slight increase in systemic arterial blood pressure may effect an increase in the perfusion pressure in the post-ischemic brain, because cerebrovascular autoregulation had been disturbed by the ischemic insult, and that this increased perfusion pressure may result in BBB change.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous autoradiographic assessment with 14 Cantipyrine" revealed a marked rCBF increase in the ischemic hemisphere of gerbils that had been exposed to 1 h ischemia when the systemic blood pressure was elevated to 130-150 mm Hg after blood flow restoration. In the same study, diffuse oligemia was noted in This led to the consideration that a slight increase in systemic arterial blood pressure may effect an increase in the perfusion pressure in the post-ischemic brain, because cerebrovascular autoregulation had been disturbed by the ischemic insult, and that this increased perfusion pressure may result in BBB change.…”
Section: Discussionmentioning
confidence: 95%
“…Neither HAL nor propranolol (PROP) reinstated deficits in the recovered animals. Other investigators have found that PBZ increases the incidence of stroke, worsens neurological symptoms, and causes high mortality in an experimental stroke model (McGraw, Pashyan, & Wendell, 1976). Additionally, a clinical study with ischemIc or infarcted patients reported that a combined treatment with PBZ and PROP worsened neurological deficits in some patients (J. S. Meyer et al, 1976).…”
Section: Discussionmentioning
confidence: 98%
“…The assessment of neurological status of the animal was carried out in 3 stages: assessment of the dynamics of neurological disorders on a McGrow scale on day 1, 3, 7 and 14 [1,5]; on the first day - …”
Section: Methodsmentioning
confidence: 99%
“…4 Солгалова А.С. 5 Анциферов О.В. 6 МОДЕЛИРОВАНИЕ ТОТАЛЬНОЙ ИШЕМИИ ГОЛОВНОГО МОЗГА У КРЫС 1) аспирант кафедры фармакологии Медицинского института НИУ «БелГУ», 308015, Белгород, ул.…”
unclassified
See 1 more Smart Citation